The function of chemical folic acid in calibration methods and neurodevelopmental disorders - Zhou, Ziqi; Wang, Meng; Fan, Qiongli; Zhao, Yan; Wang, Nianrong (Frontiers in Chemistry, 2024)
Functional molecules have been attracting increasing attention in environmental and physiological studies. In particular, folic acid (FA) could be considered a key factor in estimating, adjusting, and making decisions in the treatment of neurodevelopmental disorders. It promotes the general significance and conceptual for considering FA molecular scientific research detections, which implies related advancement in both of biological structure and detection methods. Among these applications, the FA molecule acts as a coenzyme that incorporates carbon atoms and synthesizes purines and pyrimidines. Therefore, the calibration method has real applications and can be used as a sensing platform and for detection approaches, which conveys the internal relationship between the FA molecule and physiological characterization. This mini review briefly discusses multiple FA application fields and detection pathways and could supplement their utilization in anticipation of the onset of disease.